Global Efforts towards Quality Education for All : Evidence and Reflections from an International and Comparative Educational Perspective - Chinapah, Vinayagum; Cars, Mikiko; Grinberg, Sarit (Journal of Education and Research, 2013)
In the process of constructing post-2015 development global frameworks, education is increasingly seen globally to be a powerful tool for preparing students to enter the labor market as well as to create a peaceful and sustainable society. International and comparative educational research conducted on the achievement of the EFA goals has clearly revealed that despite important efforts accomplished in many countries, there are still serious challenges in terms of the quality of education that is offered. The paper examines the extent to which a minimum Quality of Education for All (QEFA) can be reached through effective use and application of evidence-based international and comparative educational research. Global efforts to attain QEFA are examined by investigating major international surveys of learning outcomes. The case of Arab states demonstrates diverse socio economic and political contexts of each country and should be reflected in regional strategies to achieve QEFA. Evidence from data on national, regional and international assessments indicates that low achievement is globally widespread and stronger government intervention will be needed. This research demonstrates that the diversity of learning conditions and environment across and within countries should be carefully reflected into quality assurance by enhancing each individual´s learning potentials. DOI: http://dx.doi.org/10.3126/jer.v3i2.8397 Journal of Education and Research August 2013, Vol. 3, No. 2, pp. 39-58